2022
DOI: 10.3390/jcm11030856
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Telemonitoring of Pulmonary Function—3-Month Follow-Up of Home Electronic Spirometry in Patients with Duchenne Muscular Dystrophy

Abstract: Background: In patients with Duchenne Muscular Dystrophy (DMD), the respiratory system determines the quality and length of life; therefore, the search for easy and safe everyday monitoring of the pulmonary function is currently extremely important, particularly in the COVID-19 pandemic. The aim of the study was to evaluate the influence of a three-month home electronic spirometry (e-spirometry) monitoring of the pulmonary function and strength of respiratory muscles as well as the patients’ benefits from this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…A home-based mobile spirometer was a tool for self-monitoring in daily pulmonary function at home for Duchenne Muscular Dystrophy (DMD) and the detecting progression in idiopathic pulmonary fibrosis (IPF). However, it took a while for the training to use the device [ 32 , 33 ]. A home-based mobile spirometer was also used to reduce the frequency of acute exacerbation of COPD [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A home-based mobile spirometer was a tool for self-monitoring in daily pulmonary function at home for Duchenne Muscular Dystrophy (DMD) and the detecting progression in idiopathic pulmonary fibrosis (IPF). However, it took a while for the training to use the device [ 32 , 33 ]. A home-based mobile spirometer was also used to reduce the frequency of acute exacerbation of COPD [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A home-based mobile spirometer was also used to reduce the frequency of acute exacerbation of COPD [ 34 ]. Piotr et al reported 10,936 spirometries in 9855 patients were performed by 673 primary care professionals with a mobile phone-linked portable device, showed 5347 (49%) spirometry examinations met both accuracy and repeatability criteria [ 32 ]. There may be more performance plateau errors for self-using in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…However, taking into account our previous study, “E-monitoring of PULMonary function in patients with Duchenne Muscular Dystrophy at home,” (E-PULMoDMD; ClinicalTrials.gov Identifier: NCT05516745), was determined that daily regular spirometry measurements at home increase the quality and repeatability of the results obtained in the clinic and improve respiratory comfort, in some patients [ 35 ]. To improve the quality of the results obtained and to achieve greater repeatability, perhaps it should be recommended to perform more frequent measurements than those currently recommended (every 6–12 months) [ 36 ], especially since there are portable devices which can be used in homes [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that it is possible to implement the telerehabilitation of respiratory muscles in patients with DMD [ 37 , 38 ]. After the results of the current research, we now consider the concept of the combined rehabilitation of both the respiratory system and the upper limbs.…”
Section: Discussionmentioning
confidence: 99%
“…The Supplementary file S2 Figure illustrates the flow of selecting articles. The number of final studies included in this review was 14 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). An example of a study that was excluded during the full-text review was the study of Elbin et al, 2022 (33) on the satisfaction with telehealth among adolescents prior to the pandemic.…”
Section: Literature Searchmentioning
confidence: 99%